The Effect of a Course of Up-cholugi and Yup-chagi Exercises on the Kinematic Indices of the Knee and the Incidence of Bow-leggedness (Genu Varum) in Professional Taekwondo Practitioners - Taher Kashefi; Abdolrasoul Daneshjoo; Seyed Kazem Mousavi Sadati (Islamic Azad University, Hamedan Branch, 2021)
Objective: Knee brace is one of the lower limb abnormalities. This study aimed to investigate the effect of knee kinematical parameters on the development of knee Genu Varum. Methods: This study's statistical sample was 32 taekwondo practitioners with red and black belts of sports clubs in the northeast of Tehran, determined using G-Power software and in two groups of 16 people in terms of gender, age, and membership in the field. The 8-week training intervention, which included 3session of 1-hour training sessions emphasizing performing the techniques of up-chulogi and yup-chaggy, was performed for the experimental group. The control group did not have any specific activity during this period. Knee kinematic indices include naval drop size tests, tibial torsion, Q angle, androgen enterogen, internal and external hip rotation, and knee hyperextension in the two groups of healthy and injured in pre and posttest was evaluated. The data were statistically analyzed using descriptive analysis using t-test and SPSS V. 23 software.  Results: According to the study results, a significant positive relationship was observed between the variables of the selected technique of up-chology and the technique of up-chugi on the incidence of knee Genu Varum. Also, there was a significant difference between the indices of naval drop (P=0.003), torsion (P=0.006), Q angle (P=0.005) and knee hyperextension (P=0.001) in pre-test to post-test results.  Conclusion: The selected exercises have increased the distance between the knees and functional disorders. Because the braced knee may play a role in influencing athletes' negative performance and injury in training and competition, it is necessary to consider it in studies related to the prevention of potential injuries.